1994
DOI: 10.1016/0891-0618(94)90013-2
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin-, thyrotropin-releasing hormone- and substance P-immunoreactive axonal innervation of the ventrolateral dendritic bundle in the cat sacral spinal cord: An ultrastructural study

Abstract: The distribution and synaptic arrangement of thyrotropin-releasing hormone-, substance P- and enkephalin-immunoreactive axonal boutons have been studied in the ventrolateral nucleus (Onuf's nucleus) of the upper sacral spinal cord segments in the cat. For this purpose, the peroxidase-antiperoxidase immunohistochemical technique was used. Immunoreactive axonal boutons were traced in complete series of sections in order to reveal synaptic contacts with the bundled dendrites of the ventrolateral nucleus. As judge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…[13][14][15] The somatic and autonomic neural innervation of the EUS arise from Onuf's nucleus of the sacral cord. [16][17][18] The postsynaptic autonomic neurons of the EUS have a high density of serotonergic and noradrenergic terminals. Blocking the reuptake of NE and 5-HT in the pre-synaptic adrenergic nerve results in increased EUS contractility secondary to increased stimulation of the post-synaptic 5-HT and NE receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The somatic and autonomic neural innervation of the EUS arise from Onuf's nucleus of the sacral cord. [16][17][18] The postsynaptic autonomic neurons of the EUS have a high density of serotonergic and noradrenergic terminals. Blocking the reuptake of NE and 5-HT in the pre-synaptic adrenergic nerve results in increased EUS contractility secondary to increased stimulation of the post-synaptic 5-HT and NE receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated, in both human and laboratory animals, that Onuf's nucleus is densely innervated by CPON-(C-terminal Flanking Peptide of Neuropeptide Y), enkephalinand somatostatin-immunopositive fibers, suggesting an autonomic nature of these cells. In specific areas of the neuropil, dense aggregates of peptide-immunoreactive fibers are visible in the proximity of Onuf's nucleus (Gibson et al, 1988;Katagiri et al, 1988;Pullen et al, 1997). Indeed, the density of enkephalinimmunopositive varicosities is higher than over somatic neurons (Ramírez-León et al, 1994), and enkephalin fibers outline Onuf's nucleus (Gibson et al, 1988 (Gibson et al, 1988;Katagiri et al, 1988), and dopamine beta-hydroxylase (DBH)-immunoreactive fibers were described in rat Onuf's nucleus by Kojima et al (1985).…”
Section: Morphological and Neurochemical Properties Of Onuf's Nuclei mentioning
confidence: 99%
“…involvement (Kawatani et al, 1986;Pullen et al, 1997). In 1900, Onuf and colleagues (Onuf, 1900) reported that it innervates the only ischiocavernosus (and it's equivalent in females, erector clitoridis) and bulbospongiosus (or bulbocavernosus) muscles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations